(untitled) (GUB Journal of Science and Engineering, 2022)
With rising fuel demands, the carbon which is avowed as inefficient energy sources is continually declining. This method is a promiscuous way not of lowering CO2 emissions but of producing economic benefits. The physiochemical conversion of carbon dioxide into chemical (energy) goods without contamination. The production of microalgae will thus help to repair CO2 and biofuels sources. In this present work, we have done a comprehensive reviewed in this paper that carbon dioxide capture mechanism, contribution of microalgae for biomass production. As a result of using microalgae (S. platensis, Salmeriensis, and Scenedesmus dimorphus are capture maximum CO2 respectively of 1.00 and 0.81gL−1 d−1, 1.0gL−1day−1-2.8gL−1day−1 and 0.8g CO2 L−1d−1 with the production of microalgae biomass (<0.4g L-1day-1, 129.24 mg−1d−1, and 0.44gcel L−1d−1) in wastewater. The overall cost of the process is considerably reduced when these light conversion and chemical processes are combined, making carbon dioxide collection even more economically viable. Microalgae was used on extensively for biodiesel production and carbon dioxide reduction, and the processes were significantly enhanced with the use of microalgae. To conclude microalgae holds a strong promise in the 21st-century biofuel industry and environmentally friendly by capturing CO2. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 8, Dec 2021 P 29-35